2019
DOI: 10.1111/jfpp.14203
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transglutaminase‐assisted ultrasound treatment on the structure and functional properties of soy protein isolate

Abstract: In this study, the effects of transglutaminase (TG) cross‐linking on physicochemical, conformational, and functional properties of soybean protein isolate (SPI) with or without ultrasound pretreatment were investigated. Electrophoresis and free amino group analysis confirmed that the SPI was cross‐linked by TG treatment. The cross‐linked SPI showed a visible decrease in solubility and increase in apparent viscosity compared with the untreated SPI. TG catalyzed the SPI to unfold the constitutive polypeptides, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…High‐intensity ultrasound (HIU) refers to the sound wave at the power of 10‐1000 W/cm 2 and the frequency of 20‐100 kHz (Soria & Villamiel, 2010), which can be used for emulsification and homogenisation because of its cavitation effects (Chandrapala et al ., 2012). Some studies (Jambrak et al ., 2009; Tang et al ., 2009; Mu et al ., 2010; Ding et al ., 2019) and our previous works (Hu et al ., 2013a,b; Zhang et al ., 2016) noticed that HIU of soy protein could reduce aggregation, improve the hydrophobicity and solubility, which might result in denser 3D gel network to increase the gelation properties of soy protein. Moreover, some researches and our previous work demonstrated that stable emulsions could be prepared by HIU (Lin & Chen, 2008; Sui et al ., 2017; Taha et al ., 2018; Benetti et al ., 2019).…”
Section: Introductionmentioning
confidence: 62%
“…High‐intensity ultrasound (HIU) refers to the sound wave at the power of 10‐1000 W/cm 2 and the frequency of 20‐100 kHz (Soria & Villamiel, 2010), which can be used for emulsification and homogenisation because of its cavitation effects (Chandrapala et al ., 2012). Some studies (Jambrak et al ., 2009; Tang et al ., 2009; Mu et al ., 2010; Ding et al ., 2019) and our previous works (Hu et al ., 2013a,b; Zhang et al ., 2016) noticed that HIU of soy protein could reduce aggregation, improve the hydrophobicity and solubility, which might result in denser 3D gel network to increase the gelation properties of soy protein. Moreover, some researches and our previous work demonstrated that stable emulsions could be prepared by HIU (Lin & Chen, 2008; Sui et al ., 2017; Taha et al ., 2018; Benetti et al ., 2019).…”
Section: Introductionmentioning
confidence: 62%
“…The cavitation effects can disrupt interactions between the local sequences of amino acids and between different parts of the protein molecule, resulting in the changes in the secondary structures of proteins [47] . However, in soy protein isolate, Ding et al (2019) found that while ultrasonication decreased the contents of α-helixes and β-sheets, random and coil β-turn structures contents increased [48] . In jackfruit seed proteins, Resendiz-Vazquez et al (2019) reported that ultrasound processing (200–600 W, 15–30 min) significantly enhanced the content of alpha-helixes and random coils, but decreased the beta-sheet content [49] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the variation in the free SH and S-S contents existed in diverse proteins, ultrasonic conditions and processing environments. For example, previously reported results indicated that the exposure of free sulfhydryl groups buried in soybean protein isolates treated with ultrasound increased the SH content, 40 which might be attributed to the ultrasonic cavitation and shear effects that reduced the particle size of protein molecules. 18 Moreover, glycation treatment remarkably increased the SH content of BSGP, but the S-S content showed no significant variation.…”
Section: Ftir Spectramentioning
confidence: 99%